If it's not what You are looking for type in the equation solver your own equation and let us solve it.
1+x/6=-3
We simplify the equation to the form, which is simple to understand
1+x/6=-3
We move all terms containing x to the left and all other terms to the right.
+ 0.16666666666667x=-3-1
We simplify left and right side of the equation.
+ 0.16666666666667x=-4
We divide both sides of the equation by 0.16666666666667 to get x.
x=-24
| 9x-20+9x-48=58 | | (2x+3)(6x+32)= | | 5x+75+2x-21=180 | | -8+b=12 | | 10-4x=-2x | | -2-p=-13 | | 6.7=0.2x+4.5 | | 62+12m=-10 | | A-7=6 | | 3a/2=2/3 | | 31/2=2/3 | | 3x+x+(80+x)=455 | | (5-w)(5w-4)=0 | | .9-.135= | | 15y+7= | | B+15=10 | | 7(3y-2)-6y= | | 4x-5+9x+37=110 | | x^5z^4/xz^3 | | e^1/2x=2 | | 3x^4-2x^2+(-6x^5)-7x=0 | | 2x*2+4x=0 | | 4=35-X | | -6-2+(-5)=0 | | X-3+1=5x-4x+1 | | 7b-80=4 | | X-.12x=300000000 | | 30+2X=60 | | x+50=40 | | 258=29x | | x-6=3x+8 | | -75=X-41 |